A biogeographical puzzle: description of two new frog species (Microhylidae: Callulops and Choerophryne) from boulder-field habitat of Dauan Island, Torres Strait, Australia - Hoskin, Conrad J. (Zootaxa, 2025)
A targeted reptile and frog survey of Dauan Island, in the northern Torres Strait between Australia and New Guinea, found two frog species that could not be assigned to known species. These are described herein, based on differences in morphology and call to congeners. Callulops gobakula sp. nov. and Choerophryne koeypad sp. nov. are restricted to deep boulder-field habitat and are almost certainly endemic to Dauan Island. Dauan Island sits in a broad region of low microhylid diversity (northern Cape York, Torres Strait and southern New Guinea), and the species are biogeographically remarkable in being distributed well to the south of congeners. The nearest Callulops record is 200 km north (and all other records are over 280 km north of Dauan Island) and the nearest Choerophryne records are about 280 km north, associated with the Central Cordillera of New Guinea. This indicates that both genera were once much more widespread but contracted away from the Torres Strait and southern lowlands of New Guinea due to historical climate drying and loss of wet rainforests. Their persistence on Dauan Island can be attributed to climatic buffering in the deep boulder-fields in which they live. Both species currently warrant a Vulnerable IUCN listing under Criterion D2. Further surveys are required to map their distribution and abundance on Dauan Island, and to assess potential threats. The new species add two new genera to the Australian faunal list, albeit due to an arbitrary political boundary that extends Australian territory nearly to the New Guinean coast.